1974
DOI: 10.1111/j.1365-2125.1974.tb00238.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Performance After a Barbiturate (Heptabarbitone)

Abstract: 1The residual effects of heptabarbitone given overnight were studied by an adaptive tracking technique. Decrements in performance were observed at the 10 h interval after 200 mg, at the 10 h and 13 h intervals after 300 mg and at the 10 h, 13 h, 16 h and 19 h intervals after 400 mg of the drug. Decrements in performance at each interval and the persistence of the effects were dose related. 2 Subjective assessments of performance correlated with measured performance, but the subjects, as a group, over-estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

1975
1975
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 9 publications
1
39
0
Order By: Relevance
“…In the previous study on the overnight ingestion of heptabarbitone, Borland & Nicholson (1974) showed that the residual effects of this drug on adaptive tracking were related to the dose ingested. Performance was impaired (P = 0.05) to 10 h after 200 mg, to 13 h (P = 0.05) after 300 mg and to 19 h (P = 0.01) after 400 mg heptabarbitone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous study on the overnight ingestion of heptabarbitone, Borland & Nicholson (1974) showed that the residual effects of this drug on adaptive tracking were related to the dose ingested. Performance was impaired (P = 0.05) to 10 h after 200 mg, to 13 h (P = 0.05) after 300 mg and to 19 h (P = 0.01) after 400 mg heptabarbitone.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study (Borland & Nicholson, 1974) we used an adaptive tracking technique to measure change in performance after drugs. Adaptive tracking provides a continuous measure of performance and is acquired only by considerable practice.…”
Section: Introductionmentioning
confidence: 99%
“…The visuo-motor co-ordination task (Borland & Nicholson, 1974) required the subjects to position a spot inside a randomly moving circle displayed on an oscilloscope. The movement of the spot was controlled by a hand held stick.…”
Section: Methodsmentioning
confidence: 99%
“…Little work has been carried out on the effectiveness of hypnotics at unusual times, but several studies have been concerned with residual effects on performance. Many hypnotics, including the benzodiazepines, lead to impaired performance after overnight ingestion (Malpas, Rowan, Joyce & Scott, 1970;Bond & Lader, 1972Borland & Nicholson, 1974, 1975aBorland, Nicholson & Wright, 1975), but it would appear that the persistence of impaired performance after diazepam is more limited than that after nitrazepam and flurazepam hydrochloride (Borland & Nicholson, 1975a & b). 35 Diazepam may be a particularly useful hypnotic, even though it has received little attention from sleep researchers except for the brief report of Kales & Scharf (1973).…”
Section: Introductionmentioning
confidence: 99%